The Effect of Kangaroo Mother Care on Body Temperature in Infats with Low Birth Weight - Pryati Rihi; Yosefina Lagut; Meriana Bili (Indonesian Journal of Global Health Research, 2024)
The main problem experienced by babies born with low birth weight is due to the immaturity of the baby's organs as a whole. Infants who are unable to maintain body temperature due to lack of subcutaneous fat will experience hypothermia. Kangaroo mother care is an innovation with an approach between mother and baby. The purpose of this study was to determine the effect of KMC on increasing the body temperature of infants with LBW. Method: This research uses a quantitative method, Quasy Experiment design with One-group pretest and post test. Results: The results of temperature measurements after the kangaroo method intervention have increased in 30 respondents or all respondents and the ρ-value= 0.000 <0.05 from the table shows the Asymp. Sig 0.000 <0.05 which means H1 is accepted and H0 is rejected. Conclusions : Kangaroo Mother Care is done only once in low birth weight babies, there is a difference in body temperature before and after being given Kangaroo Mother Care which is done for 1 hour (60 minutes).